The time-dependency of the healing behavior of laser-scratched polymer films. (August 2021) - Abend, Marcus; Zechel, Stefan; Tianis, Lukas; Kunz, Clemens; Enke, Marcel; Dahlke, Jan; Gräf, Stephan; Müller, Frank A.; Schubert, Ulrich S.; Hager, Martin D.
Abstract: The scratch healing behavior of different polymers based on reversible interactions was investigated. For this purpose, scratches were induced via femtosecond laser ablation and were analyzed using laser-scanning microscopy. The healing process was monitored over time and the residual scratch volume was studied. Thus, healing kinetics of different self-healing polymers were obtained revealing a new three step-healing process. An initial time is required in order to start the crack closure behavior. Afterwards, a fast healing behavior followed by a final slow healing period could be observed. Consequently, this study discloses significant insights into the time-dependent healing behavior of polymeric materials. Highlights: Kinetics of the scratch healing process were studied. Three phases can be distinguished in the scratch healing process. Polymer structure influences strongly the healing process.